Structural patterns of human rights violations: context analysis, guarantees of non-repetition and transformative vocation - Vázquez Valencia, Luis Daniel (2025)
The objective of this text is to develop the structural pattern approach to human rights violations in order to identify the contexts, incentives, facilities, causes, or triggers of human rights violations, and to consider how to influence them to achieve a long-term solution through context analysis, guarantees of non-repetition, and a transformative vocation.